Characteristics of Heavy Metal Contamination in Tidal Flat Sediments and Benthic Organisms in Guangxi Coastal Zone - ZOU Yu; HUANG Yiming; CHI Jiang; ZHANG Jiayao; MENG Peixin; LIU Baolin; YANG Juan (Haiyang Kaifa yu guanli)
In order to assess the status of heavy metal pollution on tidal flats in the Guangxi coastal zone, an investigation of seven heavy metals' contents in sediments and benthic organisms was carried out from 29 sampling stations during 2021-2022. The results showed that the average contents of heavy metals in the sediments ranked in order as follows: zinc(Zn), chromium(Cr), lead(Pb), copper(Cu), arsenic(As), cadmium(Cd), and mercury(Hg). The results of Kruskal-Wallis test indicated that the contents were higher in the estuarine and aquaculture shoreline, and lower in the natural shoreline. Correlation analysis showed that most of the heavy metals in sediments were synergistic with each other and were influenced by the TOC content and particle size composition in the sedimentary environment. The Hakanson's Potential Ecological Risk Indices demonstrated that the ranking of ecological risk on heavy metal contamination in sediments was as follows: estuarine (/aquaculture) shoreline, harbor (/ecologically protected) shoreline, natural shoreline, with high risk of Cd and Hg contamination in this area. However, the average contents of heavy metals ranked differently in benthic organisms. Correlation analyses indicated that the mechanisms of uptake and enrichment of different metals in organisms may be highly variable. Moreover, the results of Kruskal-Wallis test showed that the cumulative effect of benthic organisms on heavy metals was less affected by shoreline type, but mainly related to the bioavailability of heavy metals, physiological characteristics and feeding habits of different organism groups.